Psychomotor and cognitive deficits as predictors of 5-year outcome in first-episode schizophrenia. (May 2014) - Bodén, Robert; Abrahamsson, Tore; Holm, Gunnar; Borg, Jacqueline
Abstract Background: Cognitive deficits are common in schizophrenia but the predictive value of these deficits for long-term outcome in first-episode patients is unclear. Aims: We aimed to investigate associations of performance in psychomotor and cognitive tests with a 5-year functional and symptomatic outcome. Methods: After clinical stabilization, patients with a first schizophrenia spectrum diagnosis (n = 46) were assessed for global cognitive function [Synonyms, Reasoning, and Block Design (SRB)], psychomotor speed [Trail Making Test (TMT) and finger tapping] and verbal learning (Claeson–Dahl Verbal Learning Test). The subsequent 5-year outcome regarding independent living, occupational and social function, and symptomatic remission status was assessed. Results: Low psychomotor speed was associated with poor social function 5 years later, with an odds ratio (OR) of 3.37 and a 95% confidence interval (CI) of 1.08–10.51, adjusted for antipsychotic drug use. Better performance on finger tapping with the non-dominant hand was associated with an increased risk of a 5-year symptomatic non-remission (adjusted OR = 0.42, CI 0.19–0.96). Occupational function and independent living were not significantly associated with any of the investigated tests. Conclusions: Psychomotor speed is associated with a long-term outcome regarding social function and symptom remission in patients with first-episode schizophrenia.